Tradisi Manjopuk Suami Jo Carano pada Hari Kematian Istri di Nagari Sarilamak Kabupaten Lima Puluh Kota Perspektif Maslahah - Wara Aini; Sofia Ridha (Lembaga Yasin AlSys, 2026)
Although the tradition of manjopuk suami jo carano as part of Minangkabau customary law has received attention in several studies, studies that specifically analyze this tradition in Nagari Sarilamak, Lima Puluh Kota Regency, from the perspective of maslahah remain limited. This study aims to analyze the implementation of the manjopuk suami jo carano tradition and examine its relevance from the perspective of maslahah. This study used a qualitative approach with a field research design, involving informants consisting of ninik mamak, community leaders, and husbands who had undergone the tradition, selected through purposive sampling. Data were collected through observation, semi-structured interviews, and documentation, then analyzed through the stages of data reduction, data display, and conclusion drawing and verification. The results show that the manjopuk suami jo carano tradition is still maintained as a form of respect for the husband and his family, as well as a marker of the end of the husband’s status as urang sumando after his wife has passed away. Although it does not have binding customary sanctions, this tradition continues to be practiced because it contains values of togetherness, maintains kinship ties, and strengthens interfamily relationships. From the perspective of maslahah, this tradition contains benefit because it does not contradict the principles of Islamic law and supports the realization of social harmony. The conclusion of this study affirms that the manjopuk suami jo carano tradition can be understood as a customary practice that has socio-religious value and is relevant to the principle of public benefit. The implications of this study include theoretical contributions to the development of Islamic Family Law studies through the application of maslahah theory in analyzing Minangkabau customary traditions, as well as practical implications for communities and customary stakeholders in preserving traditions that are in accordance with the values of Islamic law.